The Association of Social Capital and Self-Rated Health Between Urban Residents and Urbanized Rural Residents in Southwest China - Tianpei Ma; Tianpei Ma; Bo Gao (Frontiers Media S.A., 2021)
China has seen an accelerated process of urbanization in the past 30 years. The influence of urbanization on health is complex and primarily influenced by changes in social capital. The purpose of this research was to compare the social capital between urban residents and urbanized rural residents of southwest China and its relationship with self-rated health. It is of great significance to study the difference of social capital between urban and urbanized rural residents to help urbanized rural residents improve their social adaptability and health. Data was collected from 1,646 residents between November and December of 2017 in Chengdu. Three logistic regressions were used to investigate the association between social capital and self-rated health by controlling for demographic variables, lifestyles factors, and health status factors. We observed that urban residents' self-rated health had a higher proportion of "good" than that of urbanized rural residents (P = 0.017). After controlling for factors such as health status and demographic characteristics, participants with higher social capital had better self-rated health. Urbanized rural residents with higher community trust and belonging had better self-rated health (OR = 0.701, 95% CI = 0.503~0.978), however urban residents with higher personal social networks and family relationships had better self-rated health (OR = 0.676, 95% CI = 0.490~0.933 and OR = 0.666, 95% CI = 0.450~0.987, respectively). Different types of communities should focus on the types of social capital from different sources, so as to take more targeted measures to improve the social support of residents and improve their health. Improving residents' social trust and sense of belonging may help urbanized rural residents better adapt to the new living environment and help them complete the identity transformation.